Information model of Web-gallery taking into account user’s interests - Ryshkovets, Yu.; Zhezhnych, P. (Національний університет "Львівська політехніка", 2013)
Web-galleries which take into account user’s interests can reorganize the structure of its content according to user’s interests and peculiarities of their behaviour. Each Webgallery encompasses expositions that to some extent reveal defined thematic categories. Each exposition contains exhibits which not always fully reveal its content. Exhibits that poorly reveal the content of exposition distract users and distort their interpretation. This paper describes software architecture of Web-gallery in which user’s interests and interaction of components are taken into account.
Keywords: Web-gallery; user’s interests; linguistic variable; database